Evaluation of Electrocardiographic Parameters, Thoracic Morphometry and Vertebral Heart Size in Clinically Normal Dogs - Margarido, Maíra Prestes; Martins, Natalí Faria; da Silva Nunes, Paola Caroline; Confella-Júnior, Odair; Almeida Leite-Dellova, Deise Carla (Acta Scientiae Veterinariae, 2019)
Background: The Vertebral Heart Size (VHS) method sets standards for the evaluation of dog’s heart size from the comparison of the cardiac dimension with the length of the thoracic vertebrae through radiographic study. Electrocardiogram (ECG) is widely used in veterinary medicine for the evaluation of electrical conduction system of the heart; however, the increase of duration and amplitude of the ECG waves can suggest the increase of cardiac chambers in dogs. The scientific literature presents electrocardiographic and VHS values for dogs of different breeds and sizes; however, there is little information on the correlation of these parameters. Therefore, the aim of this study was to evaluate the amplitude and duration of ECG waves, thoracic morphometry and VHS values, in order to correlate these parameters in clinically normal dogs. Materials, Methods & Results: Twenty healthy dogs (11 females and 9 males), without breed distinction, medium sized (14.46 ± 2.92 kg) and aged between 1 and 8 years, were evaluated through physical examination, digital ECG (frontal and precordial leads) and thorax X-ray in right lateral (RL), left lateral (LL) and ventrodorsal (VD) projections. Thoracic morphometry and VHS measurements were determined as previously described. Clinical and ECG parameters were compatible with the references in all dogs evaluated. Dogs (75%) presented thorax intermediate with the depth and width ratio (D/W ratio) > 1.0. Some individual VHS values were higher than the references and the mean VHS values in VD projection was higher than in RL and LL projections (n = 20; P < 0.05). Female and male dogs did not differ among the evaluated parameters. A positive correlation was observed between thoracic morphometry and body weight (r ≥ +0.70; P < 0.001) and a negative correlation was found between the D/W ratio and VD VHS (r = -0.62; P < 0.05). No significant correlations were observed between the age, ECG parameters, thoracic morphometry and VHS measurements. Discussion: The majority of dogs presented intermediate thorax, a common characteristic for healthy dogs of different breeds. Some dogs had higher VHS values in different projections, when compared to references. The same has been reported by others authors for diferent breeds. However, there is no consensus about VHS values for all sexes, breeds and physical conformations in dogs. In agreement with other authors, the mean value of VD VHS was higher in relation to RL and LL VHS; however, RL and LL VHS did not differ. Positive and significative correlations were observed between body weight and thorax depth, and between body weight and thorax width, confirming that larger dogs had greater thoracic measurements. The thorax type could influence the VHS, when this parameter is determined by VD projection, because was observed a negative and significative correlation between the D/W ratio and VD VHS. So, the dogs with a deeper thorax may have lower VHS values. The correlation between VHS measurements and duration and amplitude of the ECG waves was weak, possibly because the dogs evaluated had no clinical and radiographic signs of cardiomegaly. The results of this work indicated that dogs of medium size, without signs of cardiovascular or pulmonary disease, may have higher values for VHS; besides that, thoracic morphometry may alter VHS measurement obtained from the VD projection. In addition, ECG parameters were not influenced by thoracic morphometry and had no correlation with VHS measurements.